Ectopic Pregnancy With Acceptor Implant - Zen, Putri Zelfitri; Yusrawati, Yusrawati (Fakultas Kedokteran Universitas Andalas, 2019)
Objective: To report a case of Ectopic pregnancy with implant receptorsMaterials and Methods: This article describes the case of a 41-year-old woman, diagnosed with an Ectopic Pregnancy on the gravid G5P4A0H4 11-12 weeks. Patients are using implant contraception, which has been used since 2009-2018 (3 installations). The patient came to the obstetrics and gynecology clinic Dr. M. Djamil Padang. The ultrasound gives the impression of Ectopic pregnancy in the infindibule tube. Analysis Ectopic pregnancy can also occur due to the influence of hormonal contraceptive use (progesterone).Results: Patient gets intervention performed laparotomy After the peritoneum is opened it appears fresh red blood amounting to Â± 500 cc filling the abdominal cavity. Blood evacuation and exploration are performed, it appears that the source of bleeding originates from the left tubal rupture (Infundibulum) Impression of the left tubal rupture (Infundibulum) ecectic ectopic pregnancy is impaired. Sinistal salpingectomy was performed.Conclusion: Ectopic pregnancy Ectopic pregnancy is all pregnancies where the ovum fertilized by spermatozoa implant and grows outside the uterine cavity endometrial.Keywords: Ectopic Pregnancy, Acceptor Implant